ANTIBIOTIKA, RESISTENSI, DAN RASIONALITAS TERAPI - Eka Rahayu Utami (SAINSTIS, 2011)
Bacterial resistance toward antibiotics has become international and serious problem. Rasional therapy campaign  has common recently, include correct  medication, precise dose, fix therapy periode and efficient cost. Microbes being resistance through some different ways for live survival. Many things can cause this resistance. In the end, there are a lot of harmful  consequences in health, economic, also public health aspect. Rational therapy, government regulation, and civil education become some crusial point in  bacterial resistance conquer strategy.Keywords: antibiotics, resistance, rational therapy.